Evaluating the impact of implementing Minimum Energy Performance Standards appliance regulation in Malaysia - Salleh S.F.; Roslan M.E.B.M.; Isa A.M. (Inderscience Publishers, 2023)
Air conditioning; Commerce; Developing countries; Domestic appliances; Emission control; Energy conservation; Compact fluorescent lamp; Electricity saving; Electricity-consumption; Fossil carbon; Local markets; Malaysia; MEPS; Minimum energy; Energy efficiency; carbon emission; compliance; cost analysis; developing world; electricity; emission control; energy efficiency; environmental impact assessment; household energy; implementation process; performance assessment; standard (reference); Malaysia